(untitled) (ACME, 2021)
Letters in manuscripts Vat. Lat. 14.834-35 have been usually connected to Giovanni Bianchetti, a noble man from Bologna who is identified as one of the trusted men of Giovanni Della Casa in Rome during apostolic nuntiature in Venice (1544-1549). After a systematic study of these two volumes, 28 new letters were rediscovered. These unpublished documents are well preserved and authentic, signed by Michele Della Torre, bishop of Ceneda and nuncio in France from september 1547 to august 1550. The main subject in these letters is the hard negotiation between the Kingdom of France, the Papal State, the Republic of Venice and the Swiss Confederacy in order to form a new alliance against Charles V. Moreover, these letters give information about war strategies put in place during the Rough Wooing. Although letters can be considered significant proof of diplomatic relations among Valois, the Farnese family and the Serenissima, we need to notice how Michele Della Torre, writing to Della Casa, especially wanted to entrust tasks to him and keep in contact with Venice’s scenario.